2021
DOI: 10.1039/d1sc02152d
|View full text |Cite|
|
Sign up to set email alerts
|

Comment on “Uncommon structural and bonding properties in Ag16B4O10” by A. Kovalevskiy, C. Yin, J. Nuss, U. Wedig, and M. Jansen, Chem. Sci., 2020, 11, 962

Abstract: ELF superbasins (dark-yellow stick and ball circuits) reveal how borate clusters (green and red spheres) play the role of crystal defects interrupting the electric conductivity of metallic silver (grey spheres).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
(17 reference statements)
2
14
0
Order By: Relevance
“…Against this background, we distinctly appreciate the efforts made by A. Lobato, Miguel Á. Salvadó, and J. Manuel Recio (LSR) in studying these phenomena at the example of the title compound. 1 While the computational results presented in the Comment article well comply with those published in our original paper, 2 the interpretations follow different routes. Whereas LSR focus on the analogy of pattern of the Electron Localization Function (ELF) in position space in the title compound with those found in elemental silver, we interpreted the electronic structure of Ag 16 B 4 O 10 , both in position and reciprocal space, also considering the interactions between cationic and anionic partial structures.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Against this background, we distinctly appreciate the efforts made by A. Lobato, Miguel Á. Salvadó, and J. Manuel Recio (LSR) in studying these phenomena at the example of the title compound. 1 While the computational results presented in the Comment article well comply with those published in our original paper, 2 the interpretations follow different routes. Whereas LSR focus on the analogy of pattern of the Electron Localization Function (ELF) in position space in the title compound with those found in elemental silver, we interpreted the electronic structure of Ag 16 B 4 O 10 , both in position and reciprocal space, also considering the interactions between cationic and anionic partial structures.…”
supporting
confidence: 70%
“…According to our experience, however, this issue is not crucial for the evaluation of the ELF. Importantly, in both studies 1,2 the most populated ELF basins within the silver substructure are found at the same sites. Yet, the exegeses of the computational results are appreciably divergent.…”
Section: The Excess Electrons In the Silver Partial Structure Of Ag 16 B 4 O 10mentioning
confidence: 73%
“…Moreover, a previous simulation result of Ag‐based honeycomb‐layered oxides [ 25 ] using the Kohn–Sham formalism [ 26 ] found only monolayered frameworks, indicative of the challenges and controversy faced by conventional and non‐conventional bonding schemes to effectively reproduce Ag‐based structures. [ 27–29 ] As such, this study not only represents a major milestone in the exploration of honeycomb‐layered oxides functionalities but also expounds on the structural expedience of honeycomb layered tellurates (Figure , Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this difference arises from the improved π-stacking interactions of the phenyl substituents in polar solvents. 65 The NCN carbon atom of the ligand backbone is a sensitive probe for 13 C{ 1 H} NMR. Upon deprotonation of the ligand and coordination towards the gold centers, a strong downfield shift starting from around 140 ppm (NCNH) to about 170 ppm (NCN) was detected in the 13 C{ 1 H} NMR spectra.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Pyykkö showed by theoretical methods that aurophilicity is mainly a consequence of dispersion forces and is enhanced by relativistic effects. 10 Although discussions about the concept are still ongoing, [11][12][13][14][15] this interpretation has been widely accepted. [16][17][18][19][20][21] Nowadays, it is common knowledge that such attractive forces are not only limited to gold cations but also observed in compounds containing other heavy-metal closed-shell cations.…”
Section: Introductionmentioning
confidence: 99%